‘Community Land Trust’. ​Um caminho alternativo às abordagens convencionais de política e planeamento através dos bens comuns urbanos - Santos, S.; Saaristo, S.-M.; Farias, A. C. C.; Lages, J. (Comuns: III Encontro de Ecologia Política, 2024)
Currently, housing affordability is shrinking, following increasing speculative real state tendencies. Alternative models to secure proper living environments and ensure the right of residents to land are central to rethinking conventional approaches to policymaking and urban planning. Developed by civil rights activists in the U.S. in the late 1960s, the Community Land Trust (CLT) is a model funded on non-speculative urbanization and collective land ownership. Arriving in continental Europe in recent years, CLTs advocate communal ownership and a shared effort to improve living conditions, a viable solution to address pressing housing issues. This paper presents the key features that contribute to the success of this model, focusing on the recognition of disenfranchised neighborhoods, the control of speculative prices, and the involvement of communities in the decisions that affect them. Additionally, the presentation addresses the viability of applying the CLT model in Portugal by exploring the existing urbanistic, legal, economic, and institutional frameworks. This work is based on a current study that crosses care practices and housing precarity in the Lisbon Metropolitan Area. Finally, by highlighting the current housing crisis and the need to secure tenure against evictions, this paper stresses the need for a new urban policy design grounded in urban commons, through a participatory and inclusive approach.